PENANGKAPAN NON-OSSEOUS TECHNETIUM-99M METHYLENE DIPHOSPHONATE (TC-99M MDP) PADA PEMERIKSAAN SIDIK TULANG - miraz hedi kusumah; Erwin Affandi (Jurnal Health Sains, 2023)
Non-osseous uptake on Tc-99m methylene diphosphonate can be caused by the processing of neoplasms, trauma, inflammatory processes, ischemic, and artifacts. Using Tc-99m MDP in bone scintigraphy imaging can show the changes in the metabolism of non-osseous lesions. Bone scintigraphy can show soft tissue lesions due to increased focal area activity. This study aimed to determine the non-osseous uptake of Tc-99m MDP in bone scintigraphy. The methods of this article were an article review of the current literature published in the last ten years until 2022 that discusses the uptake of non-osseous Tc-99m MDP on bone scintigraphy. This study found that proper identification of non-osseous uptake on bone scintigraphy can provide a diagnostic clue to the pathologic process. In conclusion, imaging of Tc-99m MDP uptake on the bone scintigraphy can provide additional information to reduce the risk of misinterpretation of bone scintigraphy results.